EFEKTIVITAS PEMBELAJARAN STATISTIK KELAS IX SMP MELALUI MODEL PEMBELAJARAN KOOPERATIF - Sugesti, Fitri Era (JURNAL E-DUMATH, 2016)
The strategy and teaching technique are needed by each teacher in order to obtainthe maximum learning achievement. However, it does not appropriate with thefact, learning achievement result on Statistics material, only 9 students from 30students who achieve the minimum learning completeness score 7. One of theefforts makes it done in solving the problem is using cooperative learning model.This study aims to determine the effectiveness of statistic materials of third gradestudents through cooperative learning model. This study is comparative study. Thepopulation was all of the third grade students at SMP N 1 Kota Agung Timur inthe academic year 2013-2014. Based on the hypothesis testing result, it proventhat cooperative learning model is effective to complete the student learningachievement of the third grade students in statistics material. So, cooperativelearning model can complete the statistics students learning achievement of thethird grade students at SMP N 1 Kota Agung Timur in the academic year 2013-2014.Keywords : effectiveness, cooperative learning, learning achievement result